Exploring Uropathogenic Bacteria and Measuring Serum IL-34 and IL-35 Levels in Women Affected by Systemic Lupus Erythematosus - Khudhur Jameel, Sanaa (Technium BioChemMed, 2025)
Systemic lupus erythematosus is an autoimmune disease occurs when the immune system mistakes self-tissue for foreign antigens, it causes organ tissue destruction in Systemic lupus erythematosus risk factors include interleukin biomarkers and urinary tract infections. The goal of this study was to identify uropathogenic bacteria in systemic lupus erythematosus patients, which is essential for avoiding serious complications. Additionally, serum levels of interleukin -34 and interleukin-35 in Systemic lupus erythematosus patients serve as a predictor biomarkers for systemic lupus erythematosus diagnosis. 65 women with systemic lupus erythematosus compare to 50 healthy controls were included in this study. Isolation and identification of uropathogenic bacteria , and use enzyme-linked immunosorbent assays to check serum levels of interleukin-34 and interleukin-35.The results revealed that E. coli accounted for 70% of the uropathogenic bacteria identified, with Proteus spp. come in second accounted 20% followed by Klebsiella spp. accounted 6%., while Enterococcus fecalis and Enterobacter spp. accounted for 2% with each. A notable rise in serum levels of IL-34 and IL-35 was observed when comparing patients with systemic lupus erythematosus illness to controls, with a P.value of less than 0.05.This study investigated that E. coli was the most frequently occurring of uropathogenic bacteria and showed higher serum levels of interleukin IL-34 and IL-35 in women with systemic lupus erythematosus.